Composite resins and ceramics: The performance of aesthetic restorative materials in dentistry (Research, Society and Development, 2025)
Dental restorations play a fundamental role in restoring both the masticatory function and the aesthetics of damaged teeth. With technological advances in dentistry, composite resins and ceramics have become the materials of choice for restorative procedures, particularly in anterior teeth. This theoretical and qualitative study aims to evaluate the performance of these materials in terms of durability, aesthetics, and biological integration with dental tissues. The relevance of this topic lies in the need to deepen scientific understanding of restorative materials, supporting evidence-based clinical decision-making and improving the quality of dental treatments. The research followed a bibliographic approach, with sources collected from databases such as PubMed, SciELO, and Google Scholar, using relevance, publication date, and credibility as selection criteria. The study was organized into three main sections: theoretical characterization of the materials, evaluation of clinical performance, and comparative analysis of existing studies discussing their advantages and limitations. The findings indicate that composite resins offer good cost-effectiveness, repairability, and aesthetic results, though they are more prone to wear and loss of brightness over time. Ceramics, in contrast, demonstrate superior mechanical strength, color stability, and aesthetic quality, making them particularly suitable for anterior restorations. It is concluded that the selection between these materials should consider each patient’s clinical and aesthetic requirements, along with the professional’s expertise. The results contribute to improving dental practice and guiding future research, with potential for presentation at academic conferences and publication in scientific journals.